Impact of integrated community-facility interventions model on neonatal mortality in rural Bangladesh- a quasi-experimental study - Tanvir M. Huda; Suman Kanti Chowdhury; Jatan Bhowmick; Sabrina Sharmin Priyanka; Mohammad Sohel Shomik; Qazi Sadeq-ur Rahman; Mizanur Rahman; Ishtiaq Mannan; Shams El Arifeen (PLoS ONE, 2023)
Background Neonatal mortality remains unacceptably high in many countries. WHO recommends that all newborns be assessed during the postnatal period and should seek prompt medical care if there is any danger sign. However, in many developing countries, only a small proportion of women receive postnatal care. Also, the quality of care in public health facilities is sub-optimal. Methods We designed an intervention package that included community health worker-assisted pregnancy and birth surveillance, post-natal visits to assess newborns on the first, third, seventh and twenty-eighth days of birth, referral for facility-based care, and establishing a newborn stabilization unit at the first level referral health facility. We did a quasi-experimental, propensity-score matched, controlled study in the Sylhet region of Bangladesh. We used a cross-sectional survey method at baseline and endline to measure the effect of our intervention. We considered two indicators for the primary outcome–(a) all-cause neonatal mortality rate and (b) case fatality of severe illness. Secondary outcomes were the proportion of neonates with signs and symptoms of severe illness who sought care in a hospital or a medically qualified provider. Results Our sample size was 9,940 live births (4,257 at baseline, 5,683 at end line). Our intervention was significantly associated with a 39% reduction (aRR = 0.61, 95% CI: 0.40–0.93; p = 0.046) in the risk of neonatal mortality and 45% reduction (aRR = 0.55, 95% CI: 0.35–0.86; p = 0.001) in the risk of case fatality of severe illness among newborns in rural Bangladesh. The intervention significantly increased the care-seeking for severe illness at the first-level referral facility (DID 36.6%; 95% CI % 27.98 to 45.22; p<0.001). Interpretation Our integrated community-facility interventions model resulted in early identification of severely sick neonates, early care seeking and improved treatment. The interventions led to a significant reduction in all-cause neonatal mortality and case fatality from severe illness.